Do Leadership Styles impact on Organizational Commitment of Workers? Evidence from Champion Breweries PLC, Nigeria - Essien, Blessing Stephen; Ekoriko, Edidiong Anthony (NIU Journal of Social Sciences; Vol. 6 Núm. 1 (2020): KIU Journal of Social Sciences, Vol. 6 No. 1, March 2020, 2020)
The question whether leadership styles impact on organizational commitment of workers is a rhetorical one that common sense answer does not suffice. It requires scientific inquiry. This study therefore undertook an exploratory investigation of the impact of autocratic, democratic and laissez-faire leadership styles on workersâ€™ punctuality, innovativeness and creativity, tasks performance, job retention and participation in decision making process among employees of Champion Breweries Plc Uyo, Akwa Ibom State, Nigeria. A total of 180 workers including managers were studied.  Questionnaires were used for data collection and the data were analyzed using simple percentages and regression analysis. Findings revealed that leadership styles influenced workers commitment. Workers were punctual to duties when democratic and autocratic leadership styles were used as against laissez-faire. Equally, democratic style of leadership had significant influence on workers innovativeness, tasks performance, job retention and participation in decision making. On the contrary autocratic and laissez-faire styles had significant negative influences on workers job retention and participation in decision making. The study recommended the use of contingency approach in the management of behaviour. Particularly, democratic leadership style should be combined with other two styles where necessary, since it had more positive influence on organizational commitment. Keywords: Leadership-styles, Organization, Commitment, Workers, Champion Breweries and Nigeria.